2016
DOI: 10.1111/dech.12262
|View full text |Cite
|
Sign up to set email alerts
|

The Double Life of Development: Empowerment, USAID and the Maoist Uprising in Nepal

Abstract: The geographies of developmental empowerment and subaltern rebellion have unexpectedly overlapped and expanded rapidly in recent years, especially in peasant societies in the global South. By examining the relationship between the long history of development programmes and the emergence of the Maoist revolution in Nepal in the 1990s, this article demonstrates how developmental ideas, particularly the notion of empowerment, can be articulated politically. The author argues that development has a double life in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The longing for bikas has shaped the idea of the Nepali nation state for years (Kramer, 2008;Pigg, 1992). While many consider the early 1950s, marked by the fall of the Rana dynasty and the emergence of foreignfunded aid initiatives, as the beginning of modern development ideologies in Nepal, the rhetoric of prosperity and progress has been prevalent since Nepal was unified under the Shah dynasty in the 18th century (Paudel, 2016;Pigg, 1992).…”
Section: Past and Present Injustices Of Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longing for bikas has shaped the idea of the Nepali nation state for years (Kramer, 2008;Pigg, 1992). While many consider the early 1950s, marked by the fall of the Rana dynasty and the emergence of foreignfunded aid initiatives, as the beginning of modern development ideologies in Nepal, the rhetoric of prosperity and progress has been prevalent since Nepal was unified under the Shah dynasty in the 18th century (Paudel, 2016;Pigg, 1992).…”
Section: Past and Present Injustices Of Recognitionmentioning
confidence: 99%
“…The project has since been promoted as Nepal's guaranteed path to development and prosperity; both themes are deeply entrenched in Nepali politics and society. Especially the notion of bikas 2 , which commonly outlines the dream of catching up with the 'West', has prevailed for decades (Mulmi, 2018;Paudel, 2016;Pigg, 1992Pigg, , 1993. In line with hegemonic development discourses, promoting economic growth and infrastructure expansion (Nightingale & Ojha, 2013), airport proponents have highlighted the economic opportunities it offers: it is estimated to serve 27 Asian countries and generate 100,000 direct and indirect jobs (Sah, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sharma (2001) showed that development is closely associated with modernity, and the recipients of modern amenities, such as piped water systems, often repositioned themselves in the development hierarchy. Both Fujikura (2003) and Paudel (2016) discussed the connection and awareness made possible by the “empowerment” schemes of development, which facilitated people's participation in the Maoist Civil War, which radically challenged caste and gender relations across rural Nepal. Mark Liechty, Karen Valentin, and Jeevan Raj Sharma, among others, provided insights on what “modernity” means to Nepali youths.…”
Section: Dependent Convenience In Rural Nepalmentioning
confidence: 99%
“…Nepal's Maoist revolution of the 1990s shocked the Himalayas and surprised the world as one of the unprecedented and unexpected political movements of the late last century. The armed uprising emerged in the western hilly area of the Rapti region and expanded throughout rural Nepal (Gellner, 2010;Paudel, 2016). Peasants were at the forefront of the rebellion, and by the end of the 10-year armed revolt, more than 80 percent of the rural villages were declared governed by people's governments led by revolutionaries (Onesto, 2005;Leve, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Peasant politics are also not entirely controlled and directed by the urban left and the proletariats either (Tamang, 2006). Instead, Nepal's peasant uprisings resemble the idea of subaltern spontaneity, but they are evolved through and informed by multilayer overlaps and encounters with dominant, national political forces, co-constituting the processes of transformation within the village dynamics and at the level of national political change simultaneously (Paudel, 2016). We may need to study Nepal's peasant politics outside the binary of 'autonomous vs subjugated' categories by mobilizing a relational approach of exploring overlaps and simultaneity.…”
Section: Introductionmentioning
confidence: 99%